A TURKISH CYPRIOT POET IN TURKISH LITERATURE: NEVZAT YALCIN AND HIS POETRY - Hüseyin EZİLMEZ (Fırat University, 2019)
Nevzat Yalçın is one of the Turkish Cypriot poets who found place in Turkish literature. Yalçın, as a member of the “Hisarcılar” literary group, as known in the history of Turkish Literature, from the beginning to the end (1950-1980); he was a loyal representative of the Hisar group with his poems, writings and ideas. He was born in 1926 in Poli, Pafos district. In 1945 he went to Turkey for his university education, and although he never lost his connection with Cyprus, he lived in Turkey, England and Germany till the end of his life. He died in Köln, Germany on the 31st of October, 2012. Although Nevzat Yalçın’s art developed in the taste and style of the Hisar Magazine’s national and traditional literature, he published his first poems in Cyprus, in the magazines and newspapers of that time. These poems were written between 1940-1950 and they are youth poems and more like imitations. In these poems, in which the poet used metrical system and syllabic meter, the influence of Folkloric poetry and Divan poetry is seen. The second period of Nevzat Yalçın’s art is the Hisar period and considered to be his prime. Most of his work was published in the Hisar magazine. He collected these poems in two books, “A” Sokağı, 1969 (“A” Street), and Güneş ve Adam, 1977 (the Sun and the Man). The themes of these poems are mostly love, longing, nature and love of the country. In the beginning he used metrical system and classic verse forms, and gradually he moved to free verse. Nevzat Yalçın, in his prime poems, masterly compounds the emotion, thought and imagination in the western way; he uses tradition a great deal; inspired by Ahmet Haşim and Yahya Kemal’s poetry, and made a synthesis out of all these. The poems written after Hisar belongs to the third period that qualify as the stagnation time. Yalçın, didn’t publish any of the poems he wrote in this period. These poems were collected by Hatem Türk and published after the poet’s death as Nevzat Yalçın Şiirler (2015). The poems of this period were unlike the poems published in Hisar, as they reflected his feelings and thought of advance age and they are quite politic. This article treats all phases of Nevzat Yalçın’s poetry and evaluates his work from the structural and contextual point of view in order to be able to analyse his poetry better, put forward and make use of his personal, spiritual and social portrait. Thus, this study’s main aim is to raise awareness about Nevzat Yalçın, a Turkish Cypriot poet and writer who found place in Turkish Literature.